Foreign exchange EURUSD forecasting: a time-series forecasting through periodic U.S. economic event announcements - Heng, Xin Peng; Chai, Jeslyn; Tan, Zheng Zhi; Woo, Wee-Liam; Yap, Yang (2019)
Foreign exchange rate would experience vigorous changes immediately after the announcement of macroeconomic data. The rates in the foreign exchange market tend to be varied corresponding to participants’ perception of positive or adverse news. This research examines the significance periodic macroeconomic announcements and the direction of EURUSD post announcements from June 2013 to May 2018. We realized that most of the macroeconomic announcements could significantly affect foreign exchange rate few hours after the announcement but they eventually lost their significance in longer period. This showed that most traders would stay alert for the announcements and trade frequently according to the macroeconomic data released. However, foreign exchange rate quoting currency of two nations can actually be influenced by countless factors. Hence, it was reasonable if certain economic data lost its significance shortly after announcements as traders might be looking forward to observing other data. Lastly, it is also pivotal to take note that macroeconomic environment is ever-changing, so there will never be a sustainable sign or direction for foreign exchange rates. Certain news might be deemed positive in certain period of time but opposite in other timeframes.